2006
DOI: 10.1002/acp.1263
|View full text |Cite
|
Sign up to set email alerts
|

Repeated recall, retention interval and the accuracy–confidence relation in eyewitness memory

Abstract: People can evaluate the quality of their memories by giving a confidence judgement concerning the perceived accuracy of what is recalled or recognised. Even when people strive for accuracy and claim great confidence they may, however, not remember what actually happened. Both accuracy and confidence can be affected by various factors. In this study, we investigated the effects of retention interval (either 1, 3 or 5 weeks delay before first testing) and of repeated questioning (initial recall after 1 week, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 37 publications
(45 reference statements)
6
57
1
1
Order By: Relevance
“…In the present study, we found that most witnesses, both sober and intoxicated, were interviewed on the same day as the crime. On the one hand, interviewing witnesses soon after the crime has the mnemonic benefit of slowing Intoxicated witnesses and suspects 16 down the rate of forgetting (Odinot & Wolters, 2006). Additionally, previous research has found that interviewing a witness multiple times helps to preserve the accuracy of memory across the retention interval in both sober (Ebbesen & Rienick, 1998) and intoxicated (Yuille & Tollestrup, 1990) participants.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that most witnesses, both sober and intoxicated, were interviewed on the same day as the crime. On the one hand, interviewing witnesses soon after the crime has the mnemonic benefit of slowing Intoxicated witnesses and suspects 16 down the rate of forgetting (Odinot & Wolters, 2006). Additionally, previous research has found that interviewing a witness multiple times helps to preserve the accuracy of memory across the retention interval in both sober (Ebbesen & Rienick, 1998) and intoxicated (Yuille & Tollestrup, 1990) participants.…”
Section: Discussionmentioning
confidence: 99%
“…Of further concern is that whereas correct recall decreases as the retention interval increases, incorrect recall does not always decrease in a comparable manner, and in some cases even increases (Larsson, Granhag, & Spjut, 2003;Tuckey & Brewer, 2003). The net effect of these patterns is that longer retention intervals often lead to memory reports that are less accurate overall (Ebbesen & Rienick, 1998;Odinot & Wolters, 2006). Moreover, long delays also provide greater opportunity for memory to become contaminated by external sources such as co-witnesses (French, Garry, & Mori, 2011;Gabbert, Memon, & Allan, 2003;Hope, Ost, Gabbert, Healey, & Lenton, 2008).…”
Section: Remembering Remotely: Would Video-mediation Impair Witnessesmentioning
confidence: 99%
“…Odinot and Wolters (2006) showed a video that ended in a traffic accident, and asked 22 open-ended questions several times. Observed calibration was apparently similar to the theoretically perfect, although the authors simply presented the calibration curve without quantifying it, thus missing some of the relevant information that calibration may have offered.…”
mentioning
confidence: 99%